Field notes contributed by Raymond L. Cummins, spring 1980 - Cummins, Raymond L.et al (1980)
List of birds and locations contributed by Raymond L. Cummins with observers Thaine Hopkins and Ronald Harms. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1980. Epson - sheet feed/flatbed